Introduction to Organic Crop Production - Danielle D. Treadwell (EDIS)
Organic farming can generally be described as a method of production that utilizes non-synthetic inputs and emphasizes biological and ecological process to improve soil quality, manage soil fertility, and optimize pest management. This revised 16-page fact sheet is written for commercial producers who are transitioning to or beginning organic production. Written by D.D. Treadwell and published by the UF Department of Horticultural Sciences, April 2014.